(untitled) (Research, Society and Development, 2020)
Kingsleya attenboroughi is a freshwater crab species belonging to Pseudothelphusidae described in the municipality of Barbalha, Ceará. The objective of this study was to understand the degree of knowledge of residents of two rural communities (Sítio Santo Antônio and Farias) of the same municipality about K. attenboroughi. The data were obtained from March to May 2018 through the application of open and semi-structured interviews, using the usual techniques of ethnographic recording. We interviewed 30 women and 22 men, whose ages ranged from 18 to 93 years. The participants provided data that can serve in a more objective way to make decisions regarding the preservation of K. attenboroughi in the Conservation Unit in which it occurs. The residents use the streams of the species for various activities, such as agriculture, farming, fishing and bathing, and pass the knowledge about the species from generation to generation. These activities, together with an aquatic theme park, can be the main causes for its threat status. All participants have been concerned about the decrease of water in recent years, damaging local biodiversity. The informants suggest activities of environmental education and greater inspection by the agencies responsible for the area.